Association of psoriasis with chronic kidney disease and end-stage renal disease: a systematic review and meta-analysis - Jing, Xu; Zhuyuan, Wen; Aijun, Chen; Jianxia, Xiong; Kun, Huang; Ping, Wang (Frontiers in Medicine, 2023)
Background and Objective: Previous studies have shown that patients with psoriasis are at higher risk of developing chronic kidney disease (CKD) and end-stage renal disease (ESRD) compared with general population; however, data on the differences in the occurrence of CKD and ESRD between patients with psoriasis and non-psoriatic controls are limited and inconsistent. The aim of this study was to carry out a comparison of the probability of suffering CKD and ESRD in patients with or without psoriasis by conducting a meta-analysis of cohort studies. Methods: Cohort studies on PubMed, Web of Science and Cochrane Library by December 2022 were searched for. The studies were screened according to pre-established inclusion criteria. Hazard ratios (HRs) and a 95% confidence intervals (CIs) for the renal outcomes among patients with psoriasis were calculated using the random-effect, generic inverse variance method. Subgroup analysis was related to the severity of psoriasis. Results: A total of seven retrospective cohort studies were included, including 738,104 psoriasis patients and 3,443,438 non-psoriasis subjects, published from 2013 to 2020. Compared to controls without psoriasis, patients with psoriasis had an increased risk of CKD and ESRD, with pooled hazard ratios of 1.65 (95% CI, 1.29-2.12) and 1.37 (95% CI, 1.14–1.64), respectively. Besides, the incidence of CKD and ESRD is positively correlated with the severity of psoriasis. Conclusion: This study showed that compared to patients without psoriasis, patients with psoriasis, especially those with severe psoriasis, had a significantly increased risk of developing CKD and ESRD. Considering the limitations of this meta-analysis, more high-quality and well-designed studies are needed in the future to validate our findings.